DEVELOPING ENGLISH LEARNERS’ ORAL PROFICIENCY WITH THE HELP OF MULTIMEDIA RESOURCES. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Considering the point that the distribution speed of different kinds of media is in parallel to worldly-recognized languages, particularly, English language, it is required to analyze their efficacy when they are blended in language learning and teaching procedure. Taking advantage of this opportunity, this article is mainly directed to examine the importance of how can multimedia resources have positive impact and contribute to the learning and teaching process of English language. It will also explore the Multimedia applications and the Internet, standards for Multimedia-language students, also teaching and learning with Multimedia. Moreover, strenuous effort was made to show some English teachers and student’s attitude towards the use of Multimedia in English language teaching.